The Papacy, the French Revolution and Napoleon - (:unkn) unknown (My University, 2017)
For the RSSO Conference on April 1, I would like to discuss the role of Popes Pius VI and VII during the French Revolution. Some issues involved are: what was the status of the Church in France before the Revolution; how important was the question of religion to the revolutionaries; how did Rome respond to these challenges; what immediate impact did the Revolution have on people of faith; and, what were the longterm consequences for the Church in France. This is an extremely interesting area of history and religion. It is regrettable that many people have little or no idea of the intensity of the attack on the Catholic Church in France and specifically on Catholics. In addition to losing all their property and religious liberties, many were exiled or murdered. When the dust settled, Napoleon came to agreement with the Church that allowed it to remain in France, but the damage was never fully repaired. I will be using general resources, such as encyclopedias, for most of this talk, with emphasis given to historians such as Eamon Duffy and John O’Malley for their treatment of the Popes and Gemma Butros for her treatment of the suppression of the convents by the revolutionaries.